1997
DOI: 10.1080/10826079708005597
|View full text |Cite
|
Sign up to set email alerts
|

DEP-FFF: Field-Flow Fractionation Using Non-Uniform Electric Fields

Abstract: Dielectrophoresis (DEP) -the movement of particles in nonuniform electric fields -can be used in combination with Field Flow Fractionation (FFF) to separate particles with differing dielectric properties. An introduction is given to the technique of DEP-FFF and its application to the separation of cells and other particles. The separation of yeast cells using the subtechniques of steric and hyperlayer DEP-FFF is demonstrated. It is shown that the hyperlayer-DEP-FFF techniques have a number of advantages, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 22 publications
3
73
0
Order By: Relevance
“…In this paper, we studied the effects of such exposure under the conditions most appropriate to DEP manipulations of cells, especially to cell DEP/FFF (field-flow fractionation) [45,46] sorting and DEP trapping [22,23,25]. Our experiments showed that under these conditions cell membrane integrity as revealed by trypan blue dye exclusion test was not compromised, and that cells were not stopped from proliferation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this paper, we studied the effects of such exposure under the conditions most appropriate to DEP manipulations of cells, especially to cell DEP/FFF (field-flow fractionation) [45,46] sorting and DEP trapping [22,23,25]. Our experiments showed that under these conditions cell membrane integrity as revealed by trypan blue dye exclusion test was not compromised, and that cells were not stopped from proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Inside a nonuniform standing field like that used in our experiments, the overall field stress also results in a nonzero dielectrophoretic force given by (4) where p(f) is the polarization factor, namely, the ratio of the voltage dropped across the bulk solution to that applied to the electrodes. This dielectrophoretic force can be made suffciently strong to overcome the sedimentation force and cause cell levitation in the sub-MHz frequency range where Re(f CM ) is negative, an effect that is exploited in cell sorters based on DEP/FFF [45,46]. Fig.…”
Section: Ac Field Induced Membrane Potential Did Not Cause the Observmentioning
confidence: 99%
“…More generalized discourse on cell dielectric properties and the physics of DEP-FFF are available elsewhere. 1,3,25,26 For the study described here, uniform cell loading, fluid flow, and AC electric field conditions were utilized so that the data from separate runs could be overlaid for comparison purposes. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The elution peak shift observed between these cells of interest and the mature, CD45-positive leukocytes indicates that the respective cell populations posses different dielectric and density properties and exemplifies the dependence of the DEP-FFF method on intrinsic morphology, size, and density differences between cell types. 1,3,25,26 In addition to separating the cells of interest from the debris and erythrocytes, we were particularly interested in the relative enrichment of the NG2-postive and nestin-positive cells in the eluted fractions after DEP-FFF processing (see Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation